Globalization, inequality and economic policy - Broll, Udo; Kemnitz, Alexander; Vivekananda Mukherjee (Economics and Business Review, 2019)
In our paper a very simple model is used to analyze the relationship between trade globalization, inequality and economic policy. Although the local government exclusively maximizes the welfare of the marginalized (unemployed) people, the inequality of relative consumption between employed and unemployed will increase with intensified trade liberalization. In contrast to this result the relative income inequality may fall in certain situations.